The effect of birth month and seasons on athlete aggression - Mahmut Gülle; Yavuz Bolat (Intelektual Pustaka Media Utama, 2021)
In this study, there were 3,335 football players from four continents from around the world formed a study universe in which the causes of athlete aggression. Also, the factors affecting athlete aggression were investigated with different variables. It has been observed that the levels of aggression of footballers are different according to the positions they play. As the number of matches that players participate in increases, aggression levels increase among the important results. A correlation was found between the ages of the footballers and their levels of aggression, but it was concluded that athletes born in December were more aggressive. Those born in January and those born in winter have shown minimal levels of aggression compared to other footballers. It has been interpreted as having higher levels of aggression, with football players born in December and winter receiving more penalties than other participants. In the continents where football players were born, the highest number of athlete aggression was observed in the participating football players from the continent of Europe, while the aggression of athletes born in the continent of Africa and Asia was found to be lower. Taking into account the data obtained from the research, it was concluded that the athlete's position, age, month, and season of birth and continent of birth are factors affecting athlete aggression.